KARAKTERISTIK BUAH, BIJI DAN KANDUNGAN MINYAK DARI TANAMAN NON PANGAN DI PULAU SERANGAN BALI - Ramdhoani, .; Arpiwi, Ni Luh; Darmadi, A.A. Ketut (Metamorfosa: Journal of Biological Sciences; Vol 5 No 1 (2018), 2018)
Various efforts to diversify energy needs to be done to overcome the scarcity of fuel in Indonesia. One of the energy diversification efforts is through the provision of usable energy fuels such as biodiesel that can be produced from vegetable oils. The aim of this research is to measure oil content of seeds from Serangan Island, South of Bali.The oil is used as biodiesel raw material.The method of this research was observation by walking around the island while collecting ripens fruits of non-food plant species. Fruits were dried and seeds were taken out. Dimension of fruit and seeds including length, breadth, and thickness were measured. Oil was extracted from seeds using soxhlet method with hexane as a solvent. Oil content was expressed as percentage of dry weight. Results showed that fruit and seed dimensions vary greatly. Oil content of seeds from highest to lowest, namely ketapang ( Terminalia catappa ) 27,06 %, kupu-kupu ( Bauhinia purpurea L.) 25,30 %, asam londo ( Pithecellobium dulce) 20,43 %, kembang merak ( Cesalphinia pulcherima ) 15,03 %, jarak kaliki ( Riccinus communis ) 14,23 %, lamtoro ( Leucaena leucocephala ) 13,86 %, tanjung ( Mimusops elengi ) 13,83 %, gorek ( Cesalpinia bonducella) 11 %, flamboyan ( Delonix regia) 10,93 %, sawo kecik ( Manilkara kauki ) 10,10 %.